Educational intervention on HIV/AIDS knowledge in adolescents - González Tielves, Marlín; Nuñez Díaz, Brenda de la Caridad; Vázquez Hernández, Aniris; Romero Díaz, Yaumara; Torres Carmona, Ivania (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Every day 5,000 young people between 15 and 24 years of age are infected with HIV, which is equivalent to almost 2 million new infections each year. Objective: to apply an educational intervention on HIV/AIDS knowledge in adolescents of the Bachelor’s Degree in Hygiene and Epidemiology of the Simón Bolívar Teaching Block, in the year 2022. Methods: Educational intervention study with quasi-experimental design. The universe was constituted by 89 students, a non-probabilistic sample of 54 was selected, an initial questionnaire was applied, a diagnosis was made and the intervention was elaborated, then the questionnaire was applied again. Descriptive statistics were used, given in absolute frequency and percentage value. Results: Most of the adolescents before the educational intervention lacked the basic knowledge and skills necessary to avoid HIV infection, had insufficient counseling, access to testing, condoms and harm reduction strategies. After the intervention was implemented, it was more successful in changing HIV/AIDS behaviors and knowledge among adolescents. Conclusions: The educational intervention on HIV/AIDS knowledge in adolescents is effective, which contributes to the prevention and control of these diseases.